Implementation of Digital Literacy as a Solution for Dissemination of Hoax News Among the Millenial Generation in Indonesia - Lutfi Uzlifatul Jannah; Luluk Muhayanah; Nur Rohmatun; Anik Asfiyatin; Sudirman Sudirman (Edumaspul: Jurnal Pendidikan, 2023)
a very important thing in overcoming the spread of hoaxes in the era of the millennial generation is the effort to generate digital literacy. The purpose of having digital literacy skills is to control oneself and the audience in interpreting confusing news on social media. This article will study the implementation of digital literacy, how it affects and how to improve skills to prevent the spread of hoax news among the millennial generation. This article uses the library research method to combine several literatures such as books, journals, and other literature. Digital literacy cannot be separated from the world of social media because 97.4% of Indonesians use social media on various platforms Digital literacy has an important meaning in the world of communication because of 3 things. everyday life. Second, millennials are addicted to digital platforms such as Google, WhatsApp, Instagram and others to find information quickly without distance and time. With digital literacy, it is hoped that the millennial generation will use social media well, be selective in sorting and selecting incoming news and messages. In the current convergence era, the millennial generation is not only a recipient but also a potential actor in spreading and producing hoax news/information